Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
[tex]\tt x=-2[/tex]
Step-by-step explanation:
[tex]\tt -3(x + 5) = -9[/tex]
Step (1) :- Distribute
[tex]\tt -3x-15=-9[/tex]
Step (2) :- Add 15 to both sides
[tex]\tt -3x-15+15=-9+15[/tex]
Step (3) :- Simplify
[tex]\tt -3x=6[/tex]
Step (4) :- Divide both sides by -3:-
[tex]\tt \cfrac{-3x}{-3}=\cfrac{6}{-3}[/tex]
[tex]\tt x=-2\;\; \bf Answer[/tex]
____
Answer:
[tex] \sf:\implies \quad {\pmb{\sf x = -2}} [/tex]
Solution:
Let's solve the given problem step by step :
[tex]:\implies \quad \sf - 3(x + 5) = - 9[/tex]
First, distribute the given problem :
[tex]:\implies \quad \sf - 3(x + 5) = - 9[/tex]
[tex] \sf:\implies \quad - (3 \times x) - (3 \times 5) = - 9[/tex]
Add 15 to both sides :
[tex] \sf:\implies \quad - 3x - 15 = - 9[/tex]
[tex] \sf:\implies \quad - 3x - 15 + 15 = - 9 + 15[/tex]
On simplifying :
[tex] \sf:\implies \quad -3x-15+15 = -9+15[/tex]
[tex] \sf:\implies \quad - 3x = 6[/tex]
Dividing both sides with same factor :
[tex] \sf:\implies \quad - 3x = 6[/tex]
[tex] \sf:\implies \quad \dfrac{ - 3x}{ - 3} = \dfrac{6}{ - 3} [/tex]
[tex] \sf:\implies \boxed{ \pmb{ \sf\quad x = - 2}}[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.